A review of animal models for post-operative pericardial adhesions - Hill, Morgan A.; Walkowiak, O. Agata; Head, William T.; Kwon, Jennie H.; Kavarana, Minoo N.; Rajab, Taufiek Konrad (Frontiers in Surgery, 2022)
Post-operative pericardial adhesions remain a serious complication after cardiac surgery that can lead to increased morbidity and mortality. Fibrous adhesions can destroy tissue planes leading to injury of surrounding vasculature, lengthening of operation time, and increased healthcare costs. While animal models are necessary for studying the formation and prevention of post-operative pericardial adhesions, a standardized animal model for inducing post-operative pericardial adhesions has not yet been established. In order to address this barrier to progress, an analysis of the literature on animal models for post-operative pericardial adhesions was performed. The animal model, method used to induce adhesions, and the time to allow development of adhesions were analyzed. Our analysis found that introduction of autologous blood into the pericardial cavity in addition to physical abrasion of the epicardium caused more severe adhesion formation in comparison to abrasion alone or abrasion with desiccation (vs. abrasion alone p=0.0002; vs. abrasion and desiccation p=0.0184). No significant correlation was found between severity of adhesions and time allowed for adhesion formation, indicating that in the pericardium, adhesion formation is complete and does not progress after 2 weeks. Finally, we found that the difference in adhesion severity in all animal species was similar, suggesting the major determinants for the choice of model are animal size, animal cost, and the availability of research tools in the particular model. This survey of the literature provides a rational guide for researchers to select the appropriate adhesion induction modality, animal model, and time allowed for the development of adhesions.